2013
DOI: 10.1128/jvi.01243-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Kaposi's Sarcoma-Associated Herpesvirus LANA Regions Important for Episome Segregation, Replication, and Persistence

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) latency-associated nuclear antigen (LANA) is a 1,162-amino-acid protein that mediates the maintenance of episomal viral genomes in latently infected cells. The two central components of episome persistence are DNA replication with each cell division and the segregation of DNA to progeny nuclei. LANA self-associates to bind KSHV terminal-repeat (TR) DNA and to mediate its replication. LANA also simultaneously binds to TR DNA and mitotic chromosomes to mediate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 70 publications
5
31
0
Order By: Relevance
“…We recently identified an internal 59-aa LANA region critical for efficient DNA replication and persistence (24,25). Here, we find that LANA recruits replication factor C (RFC), the DNA polymerase clamp [proliferating cell nuclear antigen (PCNA)] loader (26), through this sequence to mediate viral DNA replication and episome persistence.…”
Section: Oss-mentioning
confidence: 99%
“…We recently identified an internal 59-aa LANA region critical for efficient DNA replication and persistence (24,25). Here, we find that LANA recruits replication factor C (RFC), the DNA polymerase clamp [proliferating cell nuclear antigen (PCNA)] loader (26), through this sequence to mediate viral DNA replication and episome persistence.…”
Section: Oss-mentioning
confidence: 99%
“…N- and C-terminal LANA are essential for tethering KSHV DNA to mitotic chromosomes, and therefore are essential for segregation. We also recently showed that internal LANA residues 33-331 are critical for segregation(De Leon Vazquez et al, 2013). This work also showed that LANAΔ264-929 had an intermediate phenotype, consistent with amino acid 264 being near the border of sequence important for segregation.…”
Section: Resultsmentioning
confidence: 93%
“…LANA deleted for amino acids 332-929 (LANAΔ332-929) was 10.9 fold reduced for episome persistence efficiency, while LANA deleted for residues 264-929 (LANAΔ264-929) was reduced 228.6 fold (Fig. 1)(De Leon Vazquez et al, 2013). Here, we perform a targeted investigation of the region immediately upstream of the LANA internal repeat elements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting promoter is the Orf73Li promoter that drives the transcription of the latency-associated protein LANA. This protein is essential for the establishment, maintenance, and control of viral latency (76)(77)(78)(79)(80). Two other unique transcripts that are more strongly upregulated by RTA isoform 2 than RTA isoform 1 are the Orf47 and Orf49 promoters, which drive the expression of transcription that are antisense to the Orf50 region (Fig.…”
Section: Discussionmentioning
confidence: 99%